American lucifers : the dark history of artificial light, 1750-1865 - Zallen, Jeremy (University of North Carolina Press, 2019)
"American lucifers tracks how struggles to produce light transformed American history, beginning with the rise of the American whale fishery in the 1750s and culminating in the emergence, around the Civil War, of the petroleum industry and its primary product, kerosene. Between this shift from oil harvested from whales to oil extracted from rocks, American light was substantially derived from a substance called camphene, a highly explosive liquid mixture of spirits of turpentine and highly distilled alcohol, generally extracted from North Carolina pines by enslaved workers. Over the course of this narrative, Jeremy Zallen reveals the centrality of slavery to labor in gasworks, coal mines, guano islands, and factories that made illumination possible. Moreover, though the lights they created may have offered a veneer of progress and convenience, they also made it possible for industry to extract workers' and slaves' labor around the clock. The availability of these illuminants extended men's working days to the point that women and children were expected to shoulder all domestic labor as a matter of course"--